Tribological study in microscale using 3D SEM surface reconstruction. (November 2016) - Omrani, Emad; Tafti, Ahmad P.; Fathi, Mojtaba F.; Dorri Moghadam, Afsaneh; Rohatgi, Pradeep; D'Souza, Roshan M.; Yu, Zeyun
Abstract: Tribology as a branch of materials and mechanical engineering sciences incorporates concepts of friction, wear, and lubrication to discover knowledge and facts about different surfaces. The scanning electron microscope (SEM) and the optical microscope (OM) are two common imaging equipment that have been used in tribological research to visualize and characterize worn surfaces. SEMs are more practical than the OMs since: (1) they are able to generate higher resolution and increased magnification, and (2) they can also provide a greater depth of field. While SEM micrographs still remain two-dimensional (2D), tribological studies truly require information about three-dimensional (3D) surface structures. 3D surface reconstruction of SEM images is very useful in the literature since it helps to analyze the surface roughness of worn surfaces which can imply the wear and friction behavior of materials. In this contribution, copper pins were tested by pin-on-disk tribometer on three different counterfaces (aluminum as softer material, copper with the same hardness, and stainless steel as harder material) and worn surfaces further characterized by using an optimized multi-view 3D SEM surface reconstruction framework. The surface roughness of pin is also calculated by using the 3D SEM surface reconstruction algorithm. In addition, wear mechanisms were studied in further details. Results show that the COF and wear of copper pin against stainless steel are less than COF and wear of copper pin against aluminum and copper due to the formation of in situ iron rich layer on the surface. Abstract : Graphical abstract: Highlights: Develop an optimized algorithm to reconstruct 3D surface model from SEM image. Develop a method to draw surface profile from 3D surface reconstruction. Effect of counter face on tribological properties of copper alloy was investigated. Tribological properties of copper against SS are better than other counterfaces. Better tribological properties is due to formation in-situ iron rich tribolayer.